2019
DOI: 10.3329/birdem.v10i1.44761
|View full text |Cite
|
Sign up to set email alerts
|

Histomorphologic spectrum of thyroid lesions in surgically treated thyroid specimens

Abstract: Background: Diseases involving thyroid gland are myriad-they span from functional to goiterous which again can be non-neoplastic or neoplastic. The pattern and prevalence of these disorders depend on various factors like age, sex, ethnicity and geographic location of residence. The aim of the present study was to determine the pattern of thyroid lesions in surgically resected thyroid specimens.Methods: This retrospective study was conducted at Department of Histopathology of Armed Forces Institute of Pathology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
2
1
0
Order By: Relevance
“…(Table 9) In our study, thyroid malignancy was diagnosed in 5.4% (n=13) of all cases. The finding is similar to the study conducted by Raheem et al 7 (4.6%) but slightly lower than the 16% and 18% in Modi et al 8 and Haque et al 14 respectively as shown in Table 10. In this study, most of the patients had age from 30-49 years.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…(Table 9) In our study, thyroid malignancy was diagnosed in 5.4% (n=13) of all cases. The finding is similar to the study conducted by Raheem et al 7 (4.6%) but slightly lower than the 16% and 18% in Modi et al 8 and Haque et al 14 respectively as shown in Table 10. In this study, most of the patients had age from 30-49 years.…”
Section: Discussionsupporting
confidence: 89%
“…Among 242 cases, 10 cases (4.1%) were of inflammatory lesions. The same number was seen in the study conducted by Albasri et al 11 and Haque et al 14 as shown in Table 8. The most common inflammatory lesion was Hashimoto thyroiditis (80%).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation